The environmental footprint of single-use versus reusable cloths for clinical surface decontamination: a life cycle approach. (December 2022) - Maloney, B.; McKerlie, T.; Nasir, M.; Murphy, C.; Moi, M.; Mudalige, P.; Naser, N.E.; Duane, B.
Summary: Background: Global sustainability is a major health concern facing our planet today. The healthcare sector is a significant contributor to environmentally damaging activity. Reusable cloths should be considered as an environmentally friendly alternative to the predominantly used single-use surface wipes in cleaning and disinfection of environmental surfaces in healthcare settings. Aim: To conduct a rapid review of current policies on surface decontamination in healthcare settings; then to carry out a life cycle impact assessment (LCIA) of reusable cotton and microfibre cloths versus conventional single-use cloths, with three compatible disinfectants. Methods: Seven countries were included in the rapid review of policies. For the LCIA, inputs, outputs, and processes across the life cycle were included, using EcoInvent database v3.7.1 and open LCIA software. Sixteen European-recommended environmental impact categories and eight human health categories were considered. Findings: Infection prevention policies examined do not require single-use wipes for cleaning and disinfection. The disinfectant with the highest environmental impact was isopropyl alcohol. The most environmentally sustainable option for clinical surface decontamination was the microfibre cloth when used with a quaternary ammonium compound. The least environmentally sustainable option was cotton with isopropyl alcohol. Conclusion: Impacts were primarily attributed with the use of the disinfectant agent and travel processes.